Effect of Broiler Litter Based Complete Feed Fermentation Time on Nutrient Content and In vitro Digestibility - Nikomedes Anndhana Engtian Kilimpares; Raka Zacky Firzatullah; Dhita Indah Andara; Sri Mukodiningsih (Jurnal Ilmu Ternak dan Veteriner, 2021)
Broiler litter waste is increasing as the population of broiler chickens increases, on the other hand the need for ruminant feed is increasing so that alternative feeds are needed in the form of complete feed made from litter. This study was aimed to determine the effect of fermentation time on the nutritional content and digestibility of the complete feed. A completely randomized design with 4 treatments and 5 replications were applied in this study. Treatment T0 = not fermented; T1 = fermentation for 10 days; T2 = fermentation for 24 days; T3 = fermentation for 38 days. Parameters observed were nutrient content, VFA, NH3, dry matter digestibility and organic matter digestibility in vitro using cow rumen. Results showed that  fermention of complete feed with 2.5% EM4 starter and 5% probiofeed for 38 days (T3) had a significant effect (P<0.05) on nutrient content, dry matter digestibility, organic matter digestibility, VFA and NH3.  The T3 significantly affected ash content, crude fat, crude protein, BETN, TDN, dry matter digestibility, organic matter digestibility, VFA, and NH3 but had no significant effect on water content and crude fiber. It is concluded that the complete feed could be used as an alternative feed for ruminants, and it is easy to obtain, cheap and able to reduce environmental pollution.